2005
DOI: 10.1080/17453670510045462
|View full text |Cite
|
Sign up to set email alerts
|

Children with acute Perthes' disease have asymmetrical lower leg growth and abnormal collagen turnover

Abstract: Background Abnormalities in distal growth and low levels of insulin-like growth factor (IGF)-I have been reported in children with Perthes' disease. Our aim was to establish whether the acute phase of Perthes' disease is associated with abnormalities of growth, of bone or of collagen turnover.Methods We performed a cross-sectional study of 15 children (3-11 years of age, 13 boys) at acute presentation and a longitudinal cohort study of 9 children. We measured (1) the lengths of both lower legs (by knemometry) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Plasma levels of IGF-1 were reduced the first 2 years after the diagnosis of LCPD [87], but with normal levels of IGF-binding protein [88]. Low levels of IGF-1 were confirmed by Crofton et al [89], who also noted abnormal collagen turnover in the acute stages of LCPD. In plasma, nearly all the IGF-1 is bound to specific binding proteins, which for IGF-1 is the IGF-binding protein 3 (IGFBP3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma levels of IGF-1 were reduced the first 2 years after the diagnosis of LCPD [87], but with normal levels of IGF-binding protein [88]. Low levels of IGF-1 were confirmed by Crofton et al [89], who also noted abnormal collagen turnover in the acute stages of LCPD. In plasma, nearly all the IGF-1 is bound to specific binding proteins, which for IGF-1 is the IGF-binding protein 3 (IGFBP3).…”
Section: Resultsmentioning
confidence: 99%
“…Markers of type I collagen degradation are urinary deoxypyridinoline (DPD) and type I collagen telopeptide (ICTP). ICTP is higher in children with LCPD compared to controls [89], indicating an increase in type I collagen degradation. The median urinary DPD/creatinine ratio in children with LCPD is reduced during the fragmentation stage and returns to normal (if not slightly higher) in the healed stage [131] (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have also shown the presence of COL2A1 mutations in patients with Perthes disease. Crofton et al found lower soft tissue collagen synthesis and enhanced collagen breakdown in children with Perthes’ disease compared to healthy controls [ 2 ]. Su et al found a mutation of COL2A1 that caused abnormal chondrocytes, disarrangement of fibres and decreased stability in the femoral head cartilage of patients with Perthes’ disease [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the defect collagen found in patients with Perthes’ disease in these studies, a possible link between Perthes’ disease and other COL2A1-related disorders has been suggested [ 2 5 , 8 – 10 ]. However, these studies are based on small populations and different mutations in the gene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation